2014
DOI: 10.1246/cl.140231
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of Phenol in Water by Diffusive Gradients Using Thin Film Technique

Abstract: For the first time, new diffusive gradients in thin film (DGT) device using molecularly imprinted polymers as the binding agents and the nylon membrane as the diffusive layer have been developed for the sampling of phenol in water. The diffusion coefficient of phenol through the nylon membrane was 0.79 × 10−6 cm2 s−1, which was measured by the diffusion cell method. The binding agent of the DGT device was prepared by precipitation polymerization by molecularly imprinted technique using methacrylic acid as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Theoretically, DGT can be applied to any inorganic or organic diffusing species, 19 although most research so far has focused on the measurement of inorganic substances, 21,22 More recently, some studies have demonstrated applications for organic substances such as antibiotics, [23][24][25] phenol and 4-chlorophenol (4-CP), 26,27 bisphenols (BPs), 28 glyphosate and aminomethyl phosphonic acid, 29 and other polar organic contaminants in WWTPs. 30 Thus, the possibility of a DGT sampler for the wide family of HPCPs-preservatives, antioxidants and disinfectants is of great interest.…”
Section: Datmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, DGT can be applied to any inorganic or organic diffusing species, 19 although most research so far has focused on the measurement of inorganic substances, 21,22 More recently, some studies have demonstrated applications for organic substances such as antibiotics, [23][24][25] phenol and 4-chlorophenol (4-CP), 26,27 bisphenols (BPs), 28 glyphosate and aminomethyl phosphonic acid, 29 and other polar organic contaminants in WWTPs. 30 Thus, the possibility of a DGT sampler for the wide family of HPCPs-preservatives, antioxidants and disinfectants is of great interest.…”
Section: Datmentioning
confidence: 99%
“…The technique of diffusive gradients in thin-films (DGT) has provided quantitative in situ measurements of trace chemicals in aqueous systems without calibration because transport of the analyte from water to the sampler’s binding gel is controlled by molecular diffusion through the diffusive layer. , The principle of the DGT sampler, based on Fick’s first law of diffusion, has been widely reported previously. , The analyte concentration in the sampled water derived from DGT, C DGT , is expressed using eq : where M is the measured mass of target chemical accumulated in the binding gel, Δ g is the thickness of the diffusive gel layer, δ is the thickness of diffusive boundary layer (DBL), D is the diffusion coefficient of target chemical in the diffusive gel layer, t is the exposure time and A is the exposure area of the sampler. Δ g is much thicker than the typical environmental DBL thickness under most conditions, so the influence of the environmental DBL becomes negligible, making the DGT measurement fairly insensitive to hydrodynamic conditions. , eq therefore simplifies to: Theoretically, DGT can be applied to any inorganic or organic diffusing species, although most research so far has focused on the measurement of inorganic substances, , More recently, some studies have demonstrated applications for organic substances such as antibiotics, phenol and 4-chlorophenol (4-CP), , bisphenols (BPs), glyphosate and aminomethyl phosphonic acid, and other polar organic contaminants in WWTPs . Thus, the possibility of a DGT sampler for the wide family of HPCPs-preservatives, antioxidants and disinfectants is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Over 700 papers have now been published using DGT, with over 300 users in more than 30 countries. Building on this track record, DGT has been developed more recently to sample a range of organic chemicals, including antibiotics (Chen et al 2015a, Chen et al 2012, Chen et al 2013, household and personal care products (Chen et al 2017), polar organic contaminants (Challis et al 2016), anionic pesticides (Guibal et al 2017), bisphenols (Zheng et al 2015), phenol and 4-chlorophenol (Dong et al 2014a, Dong et al 2014b, glyphosate and aminomethyl phosphonic acid (Fauvelle et al 2015) and illicit drugs (Guo et al 2017). This paper develops DGT for a very important new set of selected endocrine disrupting compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research and development of DGT for organic chemicals only started in 2012, but it has already attracted considerable interest and is developing rapidly . To date, sampler development and testing of 136 organic compounds has been reported in the literature (a few from personal communication), with more being conducted. Compound classes include pharmaceuticals and personal care products, illicit drugs, endocrine-disrupting chemicals and pesticides, etc. Table S1 summarizes these publications.…”
mentioning
confidence: 99%